2013
DOI: 10.3109/10717544.2013.847032
|View full text |Cite
|
Sign up to set email alerts
|

Propolis organogel as a novel topical delivery system for treating wounds

Abstract: The formula containing 3% lecithin and 20% pluronic F127 exhibited superior skin permeation and antimicrobial activity over propolis suspension in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 15 publications
2
13
0
3
Order By: Relevance
“…Благодаря своему строению и свойствам микроэмульсии способны иммобилизовывать водо-и маслорастворимые компоненты (например, лекарства) в одну из своих несмешивающихся фаз с последующим их пролонгированным выде-лением [10][11][12]. Они могут усиливать действие лекарственных препаратов, защищать инкорпори-рованные в них вещества от деградации, использоваться для захвата токсичных веществ из разбавленной дисперсионной среды во внут-реннюю дисперсную фазу в процессах очистки, служить премиксом при получении микро-и нанокапсул [10][11][12].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Благодаря своему строению и свойствам микроэмульсии способны иммобилизовывать водо-и маслорастворимые компоненты (например, лекарства) в одну из своих несмешивающихся фаз с последующим их пролонгированным выде-лением [10][11][12]. Они могут усиливать действие лекарственных препаратов, защищать инкорпори-рованные в них вещества от деградации, использоваться для захвата токсичных веществ из разбавленной дисперсионной среды во внут-реннюю дисперсную фазу в процессах очистки, служить премиксом при получении микро-и нанокапсул [10][11][12].…”
Section: Introductionunclassified
“…Они могут усиливать действие лекарственных препаратов, защищать инкорпори-рованные в них вещества от деградации, использоваться для захвата токсичных веществ из разбавленной дисперсионной среды во внут-реннюю дисперсную фазу в процессах очистки, служить премиксом при получении микро-и нанокапсул [10][11][12]. Лиотропные жидкие кристаллы могут использоваться в качестве анизотропных матриц для получения упорядо-ченных нанообъектов [13].…”
Section: Introductionunclassified
“…Table 1 lists the classification of organogelators used widely in the preparation of organogels. Administration of drugs requires variations in the formula of organogels used, depending upon the route of drug administration (21). The advantages of organogels are reported in literature are manifold: (a) ease of preparation and administration, (b) fewer number of ingredients, which minimizes the overall production cost, (c) they act as good permeation enhancers, (d) enhanced patient compliance due to the non-toxic and non-irritating nature of the gels, (e) they act as a carrier system for the delivery of a wide variety of hydrophilic and lipophilic drugs, and (f) drug release for sustained delivery can be achieved by modifying the structure of the organogelator and the type of organic phase used (22).…”
Section: Gels In Drug Deliverymentioning
confidence: 99%
“…Bhatia et al [4] reported tamoxifen-loaded lecithin organogel for topical application. Balata et al [5] investigated propolis organogel as a novel topical delivery system for treating wounds. Topical delivery systems are employed not only to treat skin related problems, but also for complications associated with eyes, [6] nose, [7], vagina [8], or rectum [9] etc.…”
Section: Introductionmentioning
confidence: 99%